A study into the use of video probes in the kitchen: Everyday kitchen practices transforming the middle-class interiors in Turkey - Yazici, Ahmet; Tureyengil, Begum; Kaya, Cigdem (Taylor & Francis As, 2023)
The aim of the research is to understand and portray how kitchen-related practices of middle-class families in Turkey are constructed, and how they act together to form and transform the organisation and the use of the Turkish kitchen. Kitchen and cooking practices are an essential part of everyday domestic life environment and their material aspects carry meaning and knowledge that shape practices of everyday domestic life. Multiple elements that act and evolve during these practices; create new forms of interactions, structure relations among objects and people, and also transform the interior landscape. In this study, video ethnography was designed and conducted with couples to gain insight about multiple overlapping meanings embedded in practitioner's kitchen-related needs and actions, and also supported with questionnaires. Findings show that a great variety of foodstuffs and kitchen utensils depending on the richness of Turkish culinary culture requires larger and more comfortable spaces to prevent clutter.
Keywords: kitchen practices; meaning; materiality; everyday life; practice